Peningkatan Kapasitas Siswa Sekolah Menengah Atas terhadap Pengetahuan Perpajakan melalui Edukasi Pajak Interaktif - Azwad, Nugraha Abhull; Ashari, Yuli; Salsabilah, Aisyah Nur; Salsabila, Ayudia; Azizah, Nur (Journal Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
Taxation is a vital component of national economic development as it serves as the main source of government revenue. Therefore, raising tax awareness and compliance from an early age is essential to ensure the sustainability of state income. This study aims to evaluate the effectiveness of interactive tax education in improving tax understanding and awareness among students at SMK YAPMI Makassar. The methods employed include socialization activities and role-playing games based on tax-related case studies relevant to everyday life. The results show a significant improvement in both the cognitive and affective aspects of students, as evidenced by the comparison of pre-test and post-test scores, as well as increased interest and a sense of responsibility as future taxpayers. The school’s positive response opens up opportunities for the program's sustainability through regular activities or extracurricular programs. This study recommends strengthening collaboration between universities, schools, and tax authorities, as well as integrating digital technology into the learning process to create a more contextual, engaging, and sustainable educational approach. Keywords: Education; Taxation; Knowledge; Students Abstrak Perpajakan merupakan komponen vital dalam pembangunan ekonomi nasional karena berfungsi sebagai sumber utama pendapatan negara. Oleh karena itu, peningkatan kesadaran dan kepatuhan pajak sejak usia dini menjadi penting untuk menjamin keberlanjutan penerimaan negara. Penelitian ini bertujuan untuk mengevaluasi efektivitas edukasi pajak interaktif dalam meningkatkan pemahaman dan kesadaran perpajakan di kalangan siswa SMK YAPMI Makassar. Metode yang digunakan meliputi sosialisasi dan role-playing game berbasis studi kasus perpajakan yang relevan dengan kehidupan sehari-hari. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada aspek kognitif dan afektif siswa, sebagaimana dibuktikan oleh perbandingan nilai pre test dan post test, serta peningkatan minat dan rasa tanggung jawab sebagai calon wajib pajak. Respons positif dari pihak sekolah membuka peluang keberlanjutan program dalam bentuk kegiatan rutin atau ekstrakurikuler. Penelitian ini merekomendasikan penguatan kolaborasi antara perguruan tinggi, sekolah, dan otoritas pajak, serta integrasi teknologi digital dalam proses pembelajaran untuk menciptakan pendekatan edukatif yang lebih kontekstual, menarik, dan berkelanjutan. Kata Kunci: Edukasi; Perpajakan; Pengetahuan; Siswa